(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: 46,XX gonadal dysgenesis is a rare genetically heterogeneous disorder characterized by underdeveloped or absent ovaries with consequent, impuberism, primary amenorrhea, and hypergonadotropic hypogonadism. Mullerian agenesis or Mayer Rokitansky Kuster Hauser (MRKH) syndrome is characterized by congenital aplasia of the uterus and the upper part (2/3) of the vagina in a woman with normal development of secondary sexual characteristics and a normal 46,XX karyotype. The association of these two conditions is very rare and appears to be coincidental. Clinical Presentation and Intervention: We aimed to report a case of gonadal dysgenesis with MRKH. In this case report, we reported a 18-year-old girl with primary amenorrhea and underdeveloped secondary sexual characteristics. Vaginal examination revealed patent vagina. There were no other associated malformations. Her karyotype was 46, XX. The pelvic ultrasound and abdominopelvic MRI without contrast demonstrated bilateral ovarian agenesis, absence of uterus and upper part of the vagina. Hormonal substitution therapy with oral combined pill was begun. The patient has been under regular follow up for the last 1 years and showed development of secondary sexual characteristics. Conclusion: These two conditions 46, XX gonadal dysgenesis and Mullerian agenesis compromise the prognosis of fertility of young patients. Hormone substitution therapy remains the only therapeutic option. It is aimed at triggering the development of secondary sexual characters and prevent osteoporosis. There remains the unsolved problem of infertility. Bangladesh J Obstet Gynaecol, 2023; Vol. 38(2): 111-115